Short-term use of ceftriaxone sodium leads to intestinal barrier disruption and ultrastructural changes of kidney in SD rats - Wenli Zou; Yueming Liu; Wei Zhang; Bo Lin; Wei Shen; Yiwen Li; Qiang He; Juan Jin (Renal Failure)
Objective Antibiotic treatments are known to disturb gut microbiota, but their effects on the mucosal barrier and extraintestinal diseases are rarely discussed. The aim of this study was to evaluate and visualize the impact of antibiotics on colonic mucus and the microbial community, and to assess whether intestinal dysbacteriosis is involved in the pathogenesis and progression of extraintestinal diseases in vivo.Materials and Methods Twenty-one SD rats were randomly assigned into three groups followed by different experimental treatments. The albumin–creatinine ratio, urinary protein and occult blood semi-quantified test were tested. Fecal samples were collected at different time points (0,4, and 12 weeks) for 16S rRNA gene sequencing. Colon and kidney specimens were examined using light microscopy and transmission electron microscopy (TEM) to identify morphological changes.Results Ceftriaxone intervention for one week did not cause any symptoms of diarrhea or weight loss, but the alpha and beta diversities of gut microbiota decreased quickly and significantly, a lower Firmicutes/Bacteroidetes (F/B) ratio was observed. At week 12, although the alpha and beta diversities increased to a level similar to that of the control (CON) group, LEfSe analysis indicated that the microbial community composition still differed significantly in each group. In addition, KEGG metabolic prediction revealed different metabolic functions in each group. TEM examination of colon revealed that dramatic morphological changes were observed in the ceftriaxone (Cef) group, wherein microvilli were misaligned and shortened significantly and morphologically intact bacteria were seen on the epithelial cell surface. TEM examination of kidneys from the Cef group showed characteristic glomerular changes in the form of widely irregularly thickened glomerular basement membrane (GBM) and foot process fusion or effacement; mild thickening of the GBM and foot process fusion was detected when ceftriaxone and Resatorvid (TAK242, an inhibitor of TLR4 signaling) are used together in the ceftriaxone + TAK242 (TAK) group.Conclusions Short-term use of ceftriaxone induced dynamic changes of gut microbiota and lead to intestinal barrier disruption and ultrastructural changes of kidneys in the SD rats. Moreover, interference with the TLR4-dependent signaling pathway can alleviate the damage to the intestinal barrier and kidney.